2022
DOI: 10.14704/nq.2022.20.5.nq22171
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication and Characterization Behavior of Cordierite Ceramic Materials with different Molar Fraction

Abstract: The investigation was concentrated on preparation of bioactive pure cordierite ceramic and evaluate the phase transformation which excepted to form during sintering process. Cordierite prepare by chemical co precipitation, integrated Cordierite gel with water-based sol–gel which begin essentially from Alumina Al2O3, magnesium oxide MgO and silicon oxide SiO2. Different specimens were fabricated with various weight percentage of Al2O3, Mgo and SiO2 powders. All specimens were prepared in cylindrical shape by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cristobalite could result from the decomposition of the silicate minerals in the batches at all sintering temperatures (1000-1350ºC) (Table 3) in addition to its possible crystallization from the developed silicate melts [55,57]. Cristobalite appears with variable concentrations (0.10-43.30wt.%, Table 3) with no general trends in most samples.…”
Section: Phase Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cristobalite could result from the decomposition of the silicate minerals in the batches at all sintering temperatures (1000-1350ºC) (Table 3) in addition to its possible crystallization from the developed silicate melts [55,57]. Cristobalite appears with variable concentrations (0.10-43.30wt.%, Table 3) with no general trends in most samples.…”
Section: Phase Compositionmentioning
confidence: 99%
“…Cordierite begins to exist with low concentrations at 1200ºC, however, it is recognized as the main phase in all BT samples at 1300, 1350 and 1375ºC (6.20-47.00), (56.60-87.40), (47.90-86.50), and (84.10-92.50wt.%), respectively (Table 3). Cordierite is crystallized beginning from 1200ºC at the expense of enstatite, mullite, cristobalite and diopside (Table 3) [21,22,24,55,57]. This is aided by the high contents of TIOs of the batches (2.03-11.44wt.%, Table 2) which accelerates the solid-state formation of orthorhombic cordierite by lowering its crystallization temperature [20,24,27,[58][59][60].…”
Section: Phase Compositionmentioning
confidence: 99%
“…Cordierite begins to exist with low concentrations at 1200ºC, however, it is recognized as the main phase in all BT samples at 1300, 1350 and 1375ºC (6.20-47.00), (56.60-87.40), (47.90-86.50), and (84.10-92.50wt.%), respectively (Table 3). Cordierite is crystallized beginning from 1200ºC at the expense of enstatite, mullite, cristobalite and diopside (Table 3) [21,22,24,55,57]. This is aided by the high contents of TIOs of the batches (2.03-11.44wt.%, Table 2) which accelerates the solid-state formation of orthorhombic cordierite by lowering its crystallization temperature [20,24,27,[58][59][60].…”
Section: Post-sintering Characterization 321 Phase Compositionmentioning
confidence: 99%
“…The cordierite/wollastonite bio-ceramics demonstrated that the surface of these specimens had been fully coated by hydroxyapatite formation. Basheet et al [9,10] prepare cordierite system by coprecipitation method with sintering temperature 1250 o C and investigate the biotribiology behavior of cordierite by using SBF and AMTI Orth-POD wear tester.…”
Section: Introductionmentioning
confidence: 99%